Pensijilan halal Malaysia: Isu dan cabaran premis makanan Korea di Malaysia /Al ‘Uyuna Mohd Amin - Al ‘Uyuna , Mohd Amin (2022)
The Korean wave had a major impact on the entire world, and Malaysia was one of the countries that was affected. Korean influence can be found in a variety of industries, including food and beverage, cosmetics and personal care, electronics, and so on. However, the issue of applying for halal certification for Korean food premises due to the use of questionable ingredients is part of the challenges faced by Korean food premise entrepreneurs in Malaysia. Thus, this study discussed the implementation of Halal certification in Korean food premises in Malaysia as well as issues and challenges faced by premise entrepreneurs when obtaining halal certification. This study was conducted qualitatively where document analysis methods and interview sessions were implemented to meet the objectives of the study. Findings from the interviews found that five main issues in halal certification in Korean food premises have been identified, namely the use of alcohol containing ingredients from natural fermentation processes, the use of synthetic materials that can harm consumers, the small number of Korean Halal certification bodies recognized by JAKIM, the workload of Halal Executives who do not only focus on Halal as well as communication problems in the MYeHALAL system, In conclusion, most Korean food entrepreneurs want to achieve JAKIM Halal certification, but this requires a high level of commitment and cooperation from firm management to ensure that the Halal certification process is thoroughly followed.